Evaluation of the Portuguese population exposure to ionizing radiation due to x-ray and nuclear medicine procedures from 2013 to 2017. (July 2020) - Teles, P.; Trincão, M.; Alves, F.; Antunes, V.; Calado, D.; Cantinho, G.; Carvalho, A.L.; Domingues, A.; Geão, A.; Godinho, F.; Isidoro, J.; Lança, I.; et al.
Abstract: This work provides an estimation of the exposure of the Portuguese population to ionizing radiation due to radiodiagnostic (x-ray and nuclear medicine (NM)) procedures, between 2013 and 2017, using the methodology proposed by the European Commission. Obtained results show that the estimated annual mean effective dose to the Portuguese population due to x-ray procedures increased by about 16%, from 0.75 ± 0.48 mSv per caput in 2013 to 0.89 ± 0.56 mSv per caput in 2017. The x-ray exam type that contributes the most to the collective dose in Portugal is Computed Tomography (CT). In the case of nuclear medicine, an increase in the annual effective dose from 0.088 ± 0.001 mSv per caput in 2013 to 0.090 ± 0.002 mSv per caput in 2017 was observed, with the procedures that contribute the most to the collective dose being bone imaging and cardiac procedures. This study intends to raise awareness to the need of optimization of radiation dose in medical procedures. Highlights: Evaluates collective dose in Portuguese population due to radiodiagnostic exams. Studies trends for the past 8 years. Compares data with other European countries.